Karakteristik Virgin Coconut Oil Pada Perlakuan Ukuran Partikel dan Jumlah Arang Aktif Pelepah Kelapa (Cocos nucifera L.) Sebagai Adsorben - Pratysentani, Ni Kadek Listera; Yuarini, Dewa Ayu Anom; Putra, Gusti Putu Ganda (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Virgin Coconut Oil (VCO) is a pure coconut oil produced from old coconut meat in fresh conditions, which is made without heating and without using chemicals. The quality of VCO can be improved by using activated charcoal adsorbent in the filtering process. This study aims to determine the effect of particle size and amount of coconut frond activated charcoal adsorbent on VCO characteristics and determine the best treatment for particle size and amount of adsorbent to produce quality VCO. This research used a factorial randomized block design with two factors, namely particle size (P) with P1 (80 mesh), P2 (100 mesh), and P3 (120 mesh), and the amount of adsorbent (J) with J1 (20g), J2 (30g), and J3 (40g), resulting in 9 treatment combinations grouped into 2 based on the time of implementation, thus obtaining 18 experimental units.The results showed that particle size had a significant effect on water content, free fatty acids, clarity, and organoleptic characteristics such as aroma, taste, and color. Meanwhile, the amount of adsorbent from coconut frond activated charcoal had a significant effect on clarity and organoleptic characteristics such as aroma and taste, but had no significant effect on water content, free fatty acids, peroxide number, and organoleptic color. The interaction between particle size and adsorbent amount did not significantly affect the moisture content, free fatty acids, peroxide number, clarity, and organoleptic characteristics such as aroma, taste, and color of VCO. Based on these results, the best treatment to produce quality VCO products is to use a particle size of 120 mesh and the amount of activated charcoal adsorbent from coconut fronds as much as 40g. With this treatment, the values of water content 0.012 ± 0.000%, free fatty acid 0.038 ± 0.003%, clarity 0.003 ± 0.001 A, peroxide number 0.388 ± 0.003 mg ek/kg, and organoleptic test scores for taste 4.65 ± 0.59, color 4.60 ± 0.60, and aroma 4.55 ± 0.94 were obtained.